Analytic and Integrative Framework for Understanding Human Sympathetic Arterial Baroreflex Function: Equilibrium Diagram of Arterial Pressure and Plasma Norepinephrine Level - Yamasaki, Fumiyasu; Sato, Takayuki; Sato, Kyoko; Diedrich, André (Frontiers in Neuroscience, 2021)
Background: The sympathetic arterial baroreflex is a closed-loop feedback system for stabilizing arterial pressure (AP). Identification of unique functions of the closed system in humans is a challenge. Here we propose an analytic and integrative framework for identifying a static operating point and open-loop gain to characterize sympathetic arterial baroreflex in humans. Methods and Results: An equilibrium diagram with two crossing functions of mechanoneural (MN) and neuromechanical (NM) arcs was analyzed during graded tilt maneuvers in 7 healthy subjects. AP and plasma norepinephrine level (PNE), as a surrogate for sympathetic nerve activity, were recorded after vagal modulation of heart function was blocked by atropine. The MN-arc curve was described as a locus of operating points during −7°, 0°, 15°, and 60° head-up tilting (HUT) on a PNE-AP plane. The NM-arc curve was drawn as a line between operating points before and after ganglionic blockade (trimethaphan, 0.1 mg·ml-1·kg-1) during 0° or 15° HUT. Gain values were estimated from the slopes of these functional curves. Finally, an open-loop gain, which is a most important index for performance of arterial baroreflex, was given by a product of the gain values of MN (GMN) and NM arcs (GNM). GMN was 8.92 ± 3.07 mmHg·ml·pg-1; and GNM at 0° and 15° HUT were 0.61 ± 0.08 and 0.36 ± 0.05 mmHg·ml·pg-1, respectively. A postural change from supine to 15° HUT significantly reduced the open-loop gain from 5.62 ± 0.98 to 3.75±0.62. The effects of HUT on the NM arc and open-loop gain seemed to be similar to those of blood loss observed in our previous animal studies. Conclusion: An equilibrium-diagram analysis contributes to a quantitative and integrative understanding of function of human sympathetic arterial baroreflex.